Praktyczne konsekwencje zmian samorządowego systemu wyborczego w "Kodeksie wyborczym" – uwagi i refleksje na tle wyborów 2014 roku - Sieklucki, Dominik (Polityka i Społeczeństwo, 2021)
The article contains the first notes and reflections upon the consequences of changes in the Polish electoral system implemented in the Electoral Code formulated following the 2014 local–government election. The author focuses on three types of changes. The first one covers only the reforms of the local–government electoral system (e.g. changes in electoral formula or electoral districts). The second includes reforms of electoral procedures applicable to all Polish elections (voting act and candidate registration). The last one touches upon the general purpose of electoral law codification, primarily the stabilization of the electoral system.